(untitled) (Journal of the College of Basic Education, 2024)
The definition of the word “woman” is the start point at research that investigates the concept of “woman”. According to dictionary definitions of both the Merriam-Webster and the Cambridge dictionaries, a “woman” is “an adult female person”(“Woman,” n.d.) and “an adult female human being”(“Woman,” n.d.) respectively. However, the concept of woman has been investigated from different perspectives as reviewed in this paper. This research paper, nevertheless, attempts at investigating the “woman” concept in the Iraqi context in particular through a case study that is built on responses from a sample of the society. The paper adopts a feminist qualitative method that is enhanced with statistical analysis of data which makes it a mixed method paper. It is known that the Iraqi society is an eastern society that has Islam as the source of legislation. Based on that, the study poses a number of questions (as presented in Appendix 1) which lead to a concept of "woman" within the Iraqi context. The current research is meant to be the first step in formulating a holistic understanding of the concept of “woman” in the Iraqi context and trying to find the tendency formulating this concept whether it be religious, liberal, … etc. . Respondents to the survey are all Iraqis to guarantee the Iraqi context of the research. Results of the case study are discussed at the end of the paper.